2022
DOI: 10.1177/23779608221078156
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Willingness to Undertake Premarital Screening Test Among Prospective Marital Individuals

Abstract: Introduction Awareness toward premarital screening test and its influence on preventing high risk marriages has become a concern to the health care system in Oman. This is due to the increased rates of inherited diseases and genetic disorders among the Omani population secondary to consanguineous marriages. Objectives This cross-sectional study aims to describe the utilization of premarital screening tests of selected university study participants as future prospective couples. Methods The study included 400 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
2
3
4
1
Order By: Relevance
“…Furthermore, there was no statistically significant association between the age of study participants and knowledge of SCD, 23,24 and this contradicts our findings. The noticeable variations in the study finding could be attributed to the disparities in the age distributions of these two studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there was no statistically significant association between the age of study participants and knowledge of SCD, 23,24 and this contradicts our findings. The noticeable variations in the study finding could be attributed to the disparities in the age distributions of these two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the populations employed by these studies were prospective couples and those married, which could account for the differences in the findings with regard to the current study. Furthermore, there was no statistically significant association between the age of study participants and knowledge of SCD, 23,24 and this contradicts our findings. The noticeable variations in the study finding could be attributed to the disparities in the age distributions of these two studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The data were similar to those from studies in Qatar and Oman, where knowledge deficiencies have been observed regardless of understanding of the importance of PMC. 16 , 17 Our results are consistent with those from many previous studies conducted in specific populations in KSA. For instance, one study has reported that unmarried female university students had inadequate knowledge: less than one-third of participants knew which disorders are tested for.…”
Section: Discussionsupporting
confidence: 92%
“…Hal ini bisa disebabkan oleh beberapa faktor seperti ketidak tahuan responden terhadap teknologi yang dimaksud, sikap apriori indiividu untuk menolak hal baru, dan ketakutan terhadap kekeliruan atau kesalahan yang berdampak pada dosa. Faktor lain yang berpengaruh juga adalah ketidakinginan individu terhadap prosep masa depan mereka atau keturunan mereka terkait dengan penyakit genetic yang diderita (Alkalbani et al, 2022).…”
Section: Metodeunclassified